Continuous Tuning of Au–Cu2O Janus Nanostructures for Efficient Charge Separation. (29th September 2020) - Xu, Wenjia; Jia, Jia; Wang, Ti; Li, Chao; He, Bowen; Zong, Jianpeng; Wang, Yawen; Fan, Hong Jin; Xu, Hongxing; Feng, Yuhua; Chen, Hongyu
Abstract: In photocatalysis, the Schottky barrier in metal–semiconductor hybrids is known to promote charge separation, but a core–shell structure always leads to a charge build‐up and eventually shuts off the photocurrent. Here, we show that Au–Cu2 O hybrid nanostructures can be continuously tuned, particularly when the Cu2 O domains are single‐crystalline. This is in contrast to the conventional systems, where the hybrid configuration is mainly determined by the choice of materials. The distal separation of the Au–Cu2 O domains in Janus nanostructures leads to enhanced charge separation and a large improvement of the photocurrent. The activity of the Au–Cu2 O Janus structures is 5 times higher than that of the core–shell structure, and 10 times higher than that of the neat Cu2 O nanocubes. The continuous structural tuning allows to study the structure–property relationship and an optimization of the photocatalytic performance. Abstract : The distal arrangement of Au–Cu2 O domains in the Janus structure promotes charge separation, leading to a five‐ and tenfold enhancement of the photocurrent of the Au@Cu2 O core–shell structure and the neat Cu2 O nanocubes, respectively.